Myocardial Energy Response to Glyceryl Trinitrate: Physiology Revisited - Watson, William D.; Green, Peregrine G.; Valkovič, Ladislav; Herring, Neil; Neubauer, Stefan; Rider, Oliver J. (Frontiers in Physiology, 2021)
Objective Although intravenous nitrates are commonly used in clinical medicine, they have been shown to increase myocardial oxygen consumption and inhibit complex IV of the electron transport chain. As such we sought to measure whether myocardial energetics were impaired during glyceryl trinitrate (GTN) infusion. Methods 10 healthy volunteers underwent cardiac magnetic resonance imaging to assess cardiac function and 31phosphorus magnetic resonance spectroscopy to measure Phosphocreatine/ATP (PCr/ATP) ratio and creatine kinase forward rate constant (CKkf) before and during an intravenous infusion of GTN. Results During GTN infusion, mean arterial pressure (78±7 vs 65±6 mmHg, p<0.001), left ventricular (LV) stroke work (7708±2782 vs 6071±2660 ml.mmHg, p<0.001) and rate pressure product (7214±1051 vs 6929±976 mmHg.bpm, p=0.06) all fell. LV ejection fraction increased (61±3 vs 66±4%, p<0.001), with cardiac output remaining constant (6.2±1.5 vs 6.5±1.4 L/min, p=0.37). Myocardial PCr/ATP fell during GTN infusion (2.17±0.2 vs 1.99±0.22, p=0.03) with an increase in both CK kf (0.16±0.07 vs 0.25±0.1 s-1, p=0.006) and CK flux (1.8±0.8 vs 2.6±1.1 µmol/g/s, p=0.03). Conclusions During GTN infusion, despite reduced LV stroke work and maintained cardiac output, there was a 44% increase in myocardial ATP delivery through CK. As PCr/ATP fell, this increase in ATP demand coincided with GTN induced impairment of mitochondrial oxidative phosphorylation. Overall, this suggests that whilst GTN reduces cardiac work, it does so at the expense of increasing ATP demand beyond the capacity to increase ATP production.